LITERATURE REVIEW: UPAYA KEPEMIMPINAN TRANSFORMASIONAL DALAM PENERAPAN METODE MENTORSHIP SEBAGAI PENDUKUNG KESEHATAN PARIPURNA ( Literature Review: Efforts transformational leadership in methods mentorship as a support plenary health) - Prasetiani, Abigael Grace; Kusuma, Henni (Fakultas Keperawatan, Universitas Katolik Widya Mandala Surabaya, 2018)
Background: Nurse has an important role especially in achieving plenary and holistic healthcare service. Nurse is frontline in improves the safety and quality of health in health services. This need leadership in nursing, which part the base of nursing care effective and nurse recognized as a leader in patients care. Health service system will continue to metamorphosis so nurse to adopt the quality of transformational leadership. Transformational leadership allow nurse in developing health policy, transforming the health technologies, and mentorship in new nurses or student. Mentorship can be defined as a process of knowledge, attitude, and skill by professional nurse (mentor) to new nurses/student (mentee). Aim: Explain transformational leadership in mentorship method as an effort to plenary health. Method: The search this article through Google search and CINAHL with keyword mentorship, new nurses, nursing, leadership, and transformational leadership. The search got 14 article appropriate inclusion and exclusion criteria, among published in 2007-2017, in full text which are in criteria, then analysis in narrative. Results: The search data used keywords and criteria on electronic database, got 14 articles. The articles were grouped in transformational leadership, leadership in nursing, and mentorship. Conclusion: Mentorship very effective to give positive impacts to organizations health services.